Civic features. Perspectives on textbooks in Brazil in the 1970s - Santos, Márcia Regina (Historia y Memoria de la Educación, 2017)
This study addresses the different perspectives on civics and their representations in textbooks of Moral and Civic Education. For this, we have used a document consisting of three manuals used in the educational system of Florianópolis, capital of Santa Catarina / BR. We propose as our hypothesis that these documents contained elements that were responsible for social formation during the Brazilian dictatorial period. The editions studied are from the 1970s and their authors are: Jaldyr Bhering Faustino da Silva and Ayrton Capella (1971), Benedicto de Andrade (1978) and Almiro Petry, Joseph Odelso Schneider and Matthias Lenz Marinho (1972). The theoretical contribution of these works relied on the concept of representations as inscribed in Cultural History. The study highlights other dimensions of the teaching process concerning school textbooks related to the experience of historical time lived, to approaches to reading and to the multiple representations resulting from this interaction.